2021
DOI: 10.1016/j.celrep.2021.109220
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial genotoxins induce T cell senescence

Abstract: Highlights d The bacterial genotoxin CDT induces senescence and a SASP in activated CD4 T cells d ATM plays a key role in orchestrating the SASP but not in the induction of senescence d ATM orchestrates the SASP via downstream activation of the p38 MAPK d Infection with genotoxigenic bacteria increases the proportion of GL13 + T cells in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 73 publications
0
33
0
Order By: Relevance
“…Interestingly, CD4 + T lymphocytes from older individuals show diminished autophagy, accumulation of dysfunctional mitochondria, and increased ROS, leading to the phosphorylation of STAT-3 and consequently, to the production of Th17-related mediators that could trigger differentiation and activation of osteoclasts and inhibition of osteoblasts [ 87 ] ( Figure 6 ). Recently, it was reported that CDT genotoxin, a virulence factor present in pathogenic Gram-negative bacteria closely linked to periodontitis, is able to induce senescence in CD4 + T lymphocytes [ 83 ]. Moreover, DDR signaling can trigger the p38 MAPK activation and consequently, the production of a distinct SASP pattern in activated CD4 + T lymphocytes, including the production of Th17-type cytokines [ 83 ].…”
Section: P38 Mapk As a Driver Of Sasp Development In Senescent Cd4 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, CD4 + T lymphocytes from older individuals show diminished autophagy, accumulation of dysfunctional mitochondria, and increased ROS, leading to the phosphorylation of STAT-3 and consequently, to the production of Th17-related mediators that could trigger differentiation and activation of osteoclasts and inhibition of osteoblasts [ 87 ] ( Figure 6 ). Recently, it was reported that CDT genotoxin, a virulence factor present in pathogenic Gram-negative bacteria closely linked to periodontitis, is able to induce senescence in CD4 + T lymphocytes [ 83 ]. Moreover, DDR signaling can trigger the p38 MAPK activation and consequently, the production of a distinct SASP pattern in activated CD4 + T lymphocytes, including the production of Th17-type cytokines [ 83 ].…”
Section: P38 Mapk As a Driver Of Sasp Development In Senescent Cd4 ...mentioning
confidence: 99%
“…Recently, it was reported that CDT genotoxin, a virulence factor present in pathogenic Gram-negative bacteria closely linked to periodontitis, is able to induce senescence in CD4 + T lymphocytes [ 83 ]. Moreover, DDR signaling can trigger the p38 MAPK activation and consequently, the production of a distinct SASP pattern in activated CD4 + T lymphocytes, including the production of Th17-type cytokines [ 83 ]. However, it is unknown whether the activation of p38 MAPK in senescent CD4 + CD28 − T lymphocytes is responsible for the autophagic dysfunction that could eventually induce the production of a Th17-biased SASP; thus, more studies on this subject are necessary.…”
Section: P38 Mapk As a Driver Of Sasp Development In Senescent Cd4 ...mentioning
confidence: 99%
“…It is noteworthy that STING can be activated in a cGAS-independent manner [48], and more globally that IRF3 and NF-κB can be activated by other routes during the DDR [49]. Thus, CDT-induced proinflammatory response might rely on other DDR factors like ATM, as demonstrated in T cells treated with typhoid toxin [50]. Besides, cGAS has also been shown to play a crucial role during cellular senescence induced by DNA damage [51].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ATM simultaneously causes the phosphorylation of histone H2AX (gH2AX) as well as the recruitment of Mre11-Rad50-Nbs1 (MRN) complex, which provides a platform for DNA repair, and sets off checkpoint responses via the phosphorylation of CHK2 and p53, resulting in cell cycle arrest thus inhibiting cell proliferation (Figure 1) (72). In most cases, DNA damage becomes way too devastating, and the repair system fails to rescue the situation, which consequently leads to cell death (73,74) or senescence (75)(76)(77). However, in a few cases the intoxicated cells bypass death; these cells escape the built-in carcinogenesis barrier of cell death/senescence and are likely to develop a tendency for cancer formation, including genomic instability, heightened mutation frequency, and anchorage-independent cell growth (13,78,79).…”
Section: Bacterial Genotoxins and Their Biological Functionsmentioning
confidence: 99%